Los modelos pedagógicos en los programas de hipertensión arterial : entre la experiencia y los aprendizajes (2007)
ABSTRACT: to analyze the process, evaluation and systematization of hypertension programs implemented in health care services (EPS) and health institutions in Medellin (IPS). Methods: a qualitative study was conducted in 6 EPS and 26 IPS health care services. Data was collected by participative and direct observation of groups and individual who were involved in twenty educational sections. Results: the majority of EPS, educational sections attend to impact external factors of standardized individuals; educational activities are out of focus. The pedagogic model used is conventional and recurring to point out only on risk factors. Those activities don’t promote individual participation and the evaluation is based mainly on fill up records about patient’s adhesion to medications. Conclusions: the present study shows that hypertension educational programs implemented in health care services don’t meet process of the pedagogic and instructive models; therefore they can not impact positively the health of the patients participating in this program.